On the descendent Gromov-Witten theory of a K3 surface - Oberdieck, Georg (Portugaliae mathematica, 2025)
We study the reduced descendent Gromov–Witten theory of K3 surfaces in primitive curve classes. We present a conjectural closed formula for the stationary theory, which generalizes the Bryan–Leung formula. We also prove a new recursion that allows to remove descendent insertions of 1 in many instances. Together this yields an efficient way to compute a large class of invariants (modulo the conjecture on the stationary part). As a corollary we conjecture a surprising polynomial structure which underlies the Gromov–Witten invariants of the K3 surface.
Gesehen am 16.01.2026